Effects of Propofol, Low and High Doses of Remimazolam on Hemodynamic and Inflammatory Response in Laparoscopic Surgery - Deng W; Zeng Z; Liu Q; Deng J; Wang L; Li H; Zhang Y (Dove Medical Press, 2024)
Wenguang Deng, Zhiming Zeng, Qingyan Liu, Jingjing Deng, Liyu Wang, Hui Li, Yuenong Zhang The Anesthesiology Surgery Center of The Third Affiliated Hospital of Sun Yat-sen University-Yuedong Hospital, Guangdong, People's Republic of ChinaCorrespondence: Yuenong Zhang, Email 36856665@qq.comBackground: This study explored the effects of different doses of remimazolam tosilate (RT) and propofol combined with remifentanil anesthesia on hemodynamic and inflammatory responses in patients undergoing laparoscopic surgery.Subjects and Methods: Ninety patients with a BMI of less than 35 kg/m², classified as ASA II-III and scheduled for laparoscopic surgery, were enrolled in this study. Patients were divided into three groups: low-dose RT group (A), high-dose RT group (B), and propofol group (C). The changes in hemodynamic indices such as SBP, DBP, HR, MAP, and inflammatory response indices such as IL-6, SAA, CRP, and PCT, along with extubation time and doses of sufentanil, remifentanil, urapidil, and phenylephrine, were compared among the three groups.Results: There were no statistically significant differences in extubation time, doses of sufentanil and remifentanil, or the usage rates and average doses of urapidil and phenylephrine between the three groups. The average dose of phenylephrine in group A was lower than in group B and group C, with a statistically significant difference. There were no statistically significant differences among the groups in SBP, DBP, HR, and MAP from T0 to T2, nor in IL-6, SAA, CRP, or PCT levels.Conclusion: Using RT for induction and maintenance of anesthesia in laparoscopic surgery ensures stable hemodynamic and inflammatory responses in patients. Low-dose RT may reduce the usage rate and dose of vasopressors such as phenylephrine during surgery.Keywords: remimazolam tosilate, propofol, remifentanil, hemodynamic, inflammatory, laparoscopic surgery